(untitled) (Anuário Antropológico, 2018)
If you have not understood the above, do not be alarmed. You have entered the Twilight Zone of Italian politics, the rhetorical dimension of ambiguity and of metonymic shifts that lead to political mythification in the Barthian sense.1 In this paper I will explore some aspects of the rhetorics of citizenship and of individual rights in the Italian context, arguing that State threats to individual rights do not emerge as a reaction to demands for political and moral legitimacy by ethnic minorities (the “progressive” position, as is sometimes asserted in the literature), nor as a repressive attempt to deal with the contamination of political spaces by persistent “cultural” traditions such as family, patronage, clientelism, corruption, etc. (the “regressive” position). Instead, I argue that the core problem in reconciling definitions of citizenship and definitions of the self is the inability of the Italian State to localise and give meaningful content to definitions of the citizen, especially through its use of a particular rhetoric stressing personalised values such as duty and honour. In an attempt to reconcile the citizen and the individual, the State has appropriated the rhetorical forms of Catholic morality, transforming the notion of citizenship into a ritual linguistic space in which rights fail to be defined because the space is devoid of semiotic referents to local identities.2 On the other hand, citizens appropriate one of the State’s strongest metaphors, the notion of society as a social body, and give it new meaning, la Patria, in order to express their sense of distance and dissatisfaction, as well as to personalise the otherwise sterile notion of citizenship.